2020
DOI: 10.1002/er.6082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc oxide quantum dots on the photovoltaic properties of natural dye‐sensitized solar cells

Abstract: Summary Natural dyes are used as solar‐sensitive materials to construct environmentally friendly solar cells. The low efficiency of natural dyes is one of their limitations in solar cells. To solve this problem, zinc oxide quantum dots have been used as an improving agent in the development of environmentally friendly solar cells. In the current study, natural dyes were extracted from Cytisus, Alcea rosea, and Roselle flowers using the solvent method. Then, the zinc oxide quantum dots (ZnO QDs) were synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…This leads to an increase in the photocurrent density and to improve PCE. 50 The diagrammatic representation for the electron transfer mechanism of the CAISSe QDs/P-TiO 2 NFs based QDSC is displayed in Figure 9. The porous TiO 2 NFs consist of numerous nanopores, which are filled with the CAISSe QDs.…”
Section: Optical Studies Of Caisse Qds/p-tio 2 Nfsmentioning
confidence: 99%
“…This leads to an increase in the photocurrent density and to improve PCE. 50 The diagrammatic representation for the electron transfer mechanism of the CAISSe QDs/P-TiO 2 NFs based QDSC is displayed in Figure 9. The porous TiO 2 NFs consist of numerous nanopores, which are filled with the CAISSe QDs.…”
Section: Optical Studies Of Caisse Qds/p-tio 2 Nfsmentioning
confidence: 99%
“…Peymannia et al synthesized ZnO quantum dots via co-precipitation in ethanol solutions to improve the performance of dye-sensitized solar cell (DSSC). The results indicated that the efficiency of the modified solar cells with ZnO quantum dots performed 17% better than the unmodified cells [31]. In another research, ZnO nanosheets/rod hierarchical structures was used as photoanodes to fabricate DSSCs.…”
Section: Introductionmentioning
confidence: 98%
“…Besides Si-based, many advanced materials were used as the main or complementary parts of thin film- and organic-based solar cells. For instance, Cu-based ternary and quaternary compounds (e.g., CuInSe 2 (CIS), CIGS, and CuZnSnS 4 (CZTS)) act as the main absorber layer for thin film-based solar cells, ,, perovskite quantum dots function as the main absorber layer in perovskite-based solar cells, , ZnO quantum dots function as photoanodes for DSSC-based solar cells, 2D transition metal dichalcogenides (TMD) serve as an active layer, etc. Rather than searching for novel materials, conventional materials with tremendous physicochemical stability and low cost are still favorites for PV devices.…”
Section: Introductionmentioning
confidence: 99%